A review on Using Natural Products to Prevent the Compilation of Schistosomiasis - El-Shenawy, Nahla Soliman; Rashed, Hadeer Abd El-Hak; Almaaty, Ali Hussien Abu; Soliman, Maha Farid Mohamed (Jour Med Resh and Health Sci, 2021)
Genus schistosoma is a very well-preserved parasite among millions of years. Over many decades, is responsible for the morbidity and mortality of hundreds of million humans. Effective medication (Praziquantel) for acute treatment is commercially available, and prophylaxis by vaccination is promising. Where endemic Schistosomiasis is still prevalent, causing significant morbidity and mortality have far-reaching complications in many human organ systems, including irreversible pulmonary hypertension, genitourinary, central nervous system conditions, and also neoplasia. Natural products have been the source of multiple medicines for thousands of years. The discovery of pure compounds as active ingredients in plants was first described at the beginning of the 19th century. Natural products have come from variable source materials including terrestrial microorganisms, terrestrial plants, marine organisms, and terrestrial invertebrates and vertebrates. The use of drugs extracted from bacteria, fungi, plants, and marine organisms has a long common and tradition in medicine. Among these, medicinal plants include variable active principles that have been exploited against schistosomiasis syndrome, and in recent decades, natural products have attracted worldwide interest.